Viscosupplementation with Hyaluronic acid as an Adjuvant to Diacerein in improving Pain, Stiffness and Physical function in Primary Osteoarthritic Knees: a 1 year follow-up observation study - Deo Rishi Tripathi; Mahesh Kumar Talele; Amod Kumar; Harleen Uppal; Deepak Kumar (Al Ameen Medical College, 2015)
Background: In the arthritic joint, the concentration and molecular weight of hyaluronic acid are decreased by 33% to 50% because the synthesis of hyaluronic acid in OA is disrupted by increased levels of pro-inflammatory cytokines, free radicals and proteinases. The American College of Rheumatology guidelines for the treatment of osteoarthritis of the knee recommended that one treatment option to be considered is the use of intra-articular injections of hyaluronic acid for the relief of osteoarthritic pain. Objective: To describe the patient characteristics and the add-on clinical effect of viscosupplementation on physical function, pain and stiffness in patients receiving diacerein for primary knee osteoarthritis. Methods: The study recruited 39 primary osteoarthritis patients suffering from the OA for at least 6 months of which 18 were male and 21female patients age range 40-80 years and classified according to the Kellgren-Lawrence system of Grade 2-3. Intra-articular hyaluronic acid supplementation in target knee was given in OPD setting over 5 weekly doses. Results: Intensity of knee pain, stiffness, physical function of knee joint shows significant improvement for 6 months of intra-articular hyaluronic acid supplementation and non significant improvement till 1 year of follow up in primary osteoarthritic knees. Conclusion: Intraarticular hyaluronic acid viscosupplementation along with diacerin is an effective combination in the management of chronic OA pain, stiffness and maintaining physical functions over long time.